The Malleable Self: The Role of Self-Expression in Persuasion - Aaker, Jennifer L. (Journal of Marketing Research, 1999)
Considerable research in consumer experimental psychology has examined the self-expressive role of brands but has found little support for the premise that the interaction of the personality traits associated with a brand and those associated with an individual's self-concept influence attitudes. The current research focuses on the influence of the malleable self-concept on consumer attitudes toward a brand, based on the its personality associations. The results of two experiments demonstrate that traits that are made accessible by salient situational cues and those that are chronically accessible (schematic traits) positively influence consumer attitudes toward a brand based on its personality associations. More important, these effects are tested in a set of theory-based interactions that rely on the self-monitoring individual difference variable. Self congruity is enhanced for low versus high self-monitoring subjects, whereas situation congruity is enhanced for high versus low self-monitoring subjects. Together, these experiments shed light on the self-expressive use of brands and the role of the malleable self-concept in influencing consumer attitudes.